Grammatical Gender and Declension Class in Language Change: A Study of the Loss of Feminine Gender in Norwegian. Issue 3 (September 2021) - Rodina, Yulia; Westergaard, Marit
Abstract : In this paper, we investigate an ongoing change in the grammatical gender system of Norwegian. Previous research has shown that the feminine form of the indefinite article is quickly disappearing from several dialects, which has led to claims that the feminine gender is being lost from the language. We have carried out a study of the status of the feminine in possessives across five age groups of speakers of the Tromsø dialect. Our findings show that the prenominal possessives are affected by the change to the same extent as the indefinite article, while forms that have been argued not to be exponents of gender (the definite suffix and the postnominal possessive) are generally unaffected.